DIFFERENCE IN THE AEROBIC METABOLISM OF WARM AND COLD-BLOODED ANIMALS: IMPORTANCE IN THERMOGENESIS (Scientific journal of the Fergana State University, 2023)
It was discovered that cold-blooded species of animals (steppe turtle, sheltopusik (Pallas’ glass lizard) and water snake) have a very low aerobic metabolism, the level of which is about 10 times lower than that of warm-blooded rats. These data are consistent with literature data obtained on other animals. According to the modern literature, warm-blooded animals, when performing various physiological work, expend more energy than cold-blooded ones. Therefore, it is assumed that the body to maintain the warm-bloodedness spends a significant part of the metabolic energy.